135k views
5 votes
Hellllllllllllllllllllllllp

Hellllllllllllllllllllllllp-example-1
User Rocky Qi
by
5.6k points

2 Answers

5 votes

Answer:

9/25

Explanation:


(3)/(5x) - (2)/(3) = 1


(3)/(5x) = 1 + (2)/(3)

by taking LCM,


(3)/(5x) = (3)/(3) + (2)/(3)


(3)/(5x) = (3+2)/(3)


(3)/(5x) = (5)/(3)

cross multiply

5x × 5 = 3 × 3

25x = 9

x = 9/25

hope this helps you!!

User Greperror
by
6.0k points
4 votes
Sorry for my bad handwriting a notebook lol
Hellllllllllllllllllllllllp-example-1
User Ademers
by
5.9k points